Antidepressant-like effects of the Guanxin Danshen formula via mediation of the CaMK II-CREB-BDNF signalling pathway in chronic unpredictable mild stress-induced depressive rats - Xie, Weijie (Ann Transl Med, 2019)
BACKGROUND: Depression is a chronic and recurrent syndrome of mood disorder causing immense social and economic burden; thus, treatment should be improved. Guanxin Danshen formula (GXDSF), a natural botanical drug composition prescription, has significant cardiovascular protective effects and is widely used in the clinical treatment of myocardial ischaemic diseases. However, it is still unclear and seldom studied whether GXDSF has neuroprotective effects against depressive disorders. This study explored whether GXDSF has antidepressant-like effects in rats exposed to chronic unpredictable mild stress (CUMS) and analysed the possible underlying neurotrophic expression and psychotropic mechanisms. METHODS: The present study was designed to investigate the antidepressant effects of GXDSF treatment in a CUMS-induced rat model. Based on the clinical doses, the drug-treated group was intragastrically administered GXDSF for 30 days, and rats were simultaneously exposed to CUMS stimulation for 30 days. After induction and drug administration, the depression-like behaviours were determined via the sucrose preference test (SPT), the open field test (OFT), the tail suspension test (TST), and the forced swim test (FST). ELISA kits were used to examine the monoaminergic neurotransmitters, monoamine oxidase (MAO) and Ca(2+) levels in the hippocampus. Moreover, we measured and analysed the brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) levels and the upstream regulation and signal pathways of BDNF and NGF to explore their related mechanisms in this animal model of depression, including calcium-calmodulin dependent protein kinase-II (CaMKII) and cAMP response element-binding (CREB). RESULTS: The results revealed that GXDSF may possess significant antidepressant-like effects via improving body weight, raising the sucrose preference in the SPT, increasing the total distance, the number of upright stands, and the residence time of the central zone in the open field test (OPF) and reducing the immobility time in the TST and FST. In addition, GXDSF significantly upregulated the relative levels of neurotransmitters, including dopamine (DA), norepinephrine (NE), and serotonin (5-HT), in a dose-dependent manner and inhibited MAO activities in the hippocampus. Moreover, GXDSF reversed the decline in intracellular CREB and p-CREB expression induced by CUMS, downregulated the phosphorylation levels of intracellular CaMKII and its two subunits CaMKIIα and CaMKIIβ in the hippocampus, and thus, clearly upregulated the downstream effector protein expression levels of BDNF, NGF, and synitaxine-1 in the hippocampus. These data suggest that the antidepressant effects of GXDSF have a potential relationship with regulating changes in the CaMKII-CREB-BDNF pathway. CONCLUSIONS: Despite several limitations of this study, the results have suggested that GXDSF administration possesses antidepressant-like effects in CUMS-treated rats and provide the first in vivo demonstration of a possible mechanism of GXDSF via regulating changes in the CaMKII-CREB-BDNF signalling pathway. These findings provide a novel potential substrate by which herbal antidepressants may exert therapeutic effects in the treatment of depression.